[Lava Rock Covering Houses] - Streng, Evelyn Fiedler (1975)
Photograph of black lava covering a home on Heimaey. The white house covered in metal panels sits surrounded by the black lava. Hills of the lava cover the roof of the house and background. Stone and rubble dot along the black rock to the left. The sky above is clouded and white.